The determinants of bootstrap financing in crises: evidence from entrepreneurial ventures in the COVID-19 pandemic - Joern H. Block; Christian Fisch; Mirko Hirschmann (Small Business Economics, 2021)
Bootstrap financing refers to measures that entrepreneurial ventures undertake to preserve liquidity (e.g., reducing expenses, collecting receivables, delaying payments, preselling). Prior research shows that bootstrap financing is an important enabler for the growth of resource-constrained early-stage ventures. However, little is known about the use of bootstrap financing in crises, during which the preservation of liquidity is particularly salient. We investigate the determinants of bootstrap financing in the 2020 COVID-19 crisis using a sample of 17,046 German entrepreneurial ventures. We formulate hypotheses about the determinants of bootstrap financing from a necessity, human capital, and opportunity cost perspective. Among others, our results show that the severity of the crisis for the venture, the level of private consumption, and self-employment experience are positively associated with an increased use of bootstrap financing measures. Our study contributes to the literature on bootstrap financing and illuminates how entrepreneurial ventures maintain liquidity in crises. Plain English Summary Economic downturns or crises often lead to financial distress for ventures. To survive such tumultuous times, ventures need to preserve their liquidity. Bootstrap financing refers to measures that entrepreneurial ventures take to preserve liquidity (like sending payment reminders, paying invoices later, reducing tax advances, reducing commercial rent). Because little is known about how bootstrap financing is used during crises, we investigate how it was used during the COVID-19 crisis. Our study builds on a survey of 17,046 German entrepreneurial ventures and self-employed individuals. We find that the use of bootstrap financing is positively related to how severe the crisis was for the venture along with the level of private consumption and self-employment experience of the venture's owner. In contrast, a negative association exists with private liquidity, business liquidity, how long before the owner retires, and part-time self-employment. The positive association between self-employment experience and bootstrap financing indicates that targeted entrepreneurship education programs or webinars should focus on inexperienced entrepreneurs so that these individuals are prepared to use bootstrapping methods to maintain liquidity during crises.
Keywords: G30; L26; M13; 330; Entrepreneurship; Bootstrap finance; COVID-19; Crises; Coronavirus